Urban gardening and neglected and underutilized species in Salvador, Bahia, Brazil - Manuela Alves da Cunha; Lidice Almeida Arlego Paraguassú; José Geraldo de Aquino Assis; Arthur Benjamin de Paula Carvalho Silva; Ryzia de Cassia Vieira Cardoso (BMC, 2020)
Abstract Background Urban agriculture has been evidenced as a food production and environmental sustainability strategy, although it faces many obstacles in Latin American countries. Additionally, in urban areas, low consumption of fruit and greenery is noticeable, along with loss in food diversity, including the neglected and underutilized species (NUS), which involve potential to strengthen local food systems. For this reason, this work has sought to map urban gardens in the city of Salvador, Bahia, Brazil, characterizing their gardeners, and to systematize information regarding food produced and the use of NUS. Methods The municipality's urban gardens were mapped and data was collected from the gardeners. The study included two steps: (i) garden localization; (ii) on-site visits for interviews with gardeners and verification of cultivated food, destination of production, availability, and use of NUS. Results Eighteen active food gardens were located, seventeen of which participated in the study: eight (8) communal (UCG) and nine (9) private (UPG). Respondents were on average 55.76 years old, mostly (52.9%) male, working at UPG (88.9%). Women predominated in the UCG (87.5%), with higher levels of education. For 52.9% of the interviewees, the garden was their main source of income. Food produced at the urban gardens was consumed by 82.4% of the gardeners and their families. In 70.6% of the gardens, production was also sold, while 47.1% donated. During the survey, 59 NUS were found and 76.5% of respondents reported consuming 19 of the species. NUS leaves, fruits, and seeds were found to be eaten raw, boiled, or sautéed in various preparations, especially Coleus amboinicus Lour. (76.5%), Eryngium foetidum L. (35.3%), Talinum fruticosum (L.) Juss., and Pereskia aculeata Mill (both 29.4%). Occurrence and utilization of NUS did not present significant associations with the gardens or gardeners (p > 0.05). Conclusions Salvador urban gardens, even in small numbers and without government support, have produced affordable food for the local population, preserved food diversity, and the tradition of NUS cultivation and use. Thus, urban gardens are reaffirmed as relevant spaces that should be included in public policies in order to promote food and nutritional security, biodiversity, and urban environmental sustainability.